Comparison of nickel and methylene blue removal efficiency using mango seed kernel powder - Thinakaran Subramaniam (School of Environmental Engineering University Malaysia Perlis, 2011)
Biosorption has emerged as a new technology compared to conventional method like chemical precipitation for removal metal and dye from aqueous solution. In this present study, dried Mango Seed Kernel Powder (MSKP) was used as a biosorbent for Nickel (Ni) and Methylene Blue (MB) removal from aqueous solution. The removal characteristic of Ni and MB by dried MSKP were evaluated as a function of contact time, pH and initial adsorbate concerntration. the studied is to develop adsorption process. The percent Ni uptake was analyze the suitability of the adsorption process. the percent Ni uptake was analyzed with UV VIS spectrophotometer. At optimal conditions, Ni and MB uptake increased when contact time increased until reach the equilibrium time was just 20% for Ni from 45 up to 150 minutes and 90% for MB at 180 up to 300 minutes.